Assessment of Implementation of the University of Rizal System Faculty’s Extension Activities - Magdalena, Evelyn P.; Avecilla, Leni A.; Cabilin, Janeta S.; Timog, Yonie SD.; Angeles, Perlita M.; Peñano, Leonora J.; Lomangaya, Wilma R.; Angeles, Zenaida S.; Llaneta, Raquel F.; Blanquisco, Helen R.; Pateña, Elenita P. (ASEAN Journal of Education, 2016)
At the core of every higher education institutions’ aim is strengthening two of their four-fold functions, which are instruction and extension, to enable them to provide free access to functional literacy and livelihood programs among indigent communities. It is along this premise that this study aimed to assess the implementation of University of Rizal System’s literacy and livelihood extension activities in one of the communities in the eastern part of Rizal province. The study used a descriptive-evaluative research design, utilizing purposive random sampling technique and the Focus Group Discussion (FGD) to further validate the responses of the beneficiaries in the livelihood activities and in the literacy program, respectively. The results revealed that the respondents of the study evaluated the extension activities outstanding in all aspects. Planning and management and strategies both obtained a mean of 4.42, faculty trainer’s expertise had a mean of 4.45, and involvement of the participants obtained an average mean of 4.35. It was concluded, therefore, that the URS faculty’s culture of conducting extension activities is well-implemented and it truly addressed and augmented the needs of the beneficiaries in the community.